(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to investigate the effect of traditional games (hadang and This study aimed to investigate the effect of dribbling training variations on improving ball dribbling speed in futsal players at SMKN 1 Jambi City extracurricular program. This research employed an experimental method with a "One Group Pre-test Post-test Design". The population consisted of 20 futsal players from SMKN 1 Jambi City, with 10 players selected as samples using a purposive sampling technique. The training variations included slalom dribbling, sole dribbling, futsal mirror dribbling, and zig-zag run exercises conducted over 16 sessions with 4 sessions per week. The research instrument used the Figure-Eight Dribbling Test to measure dribbling speed. Data were analyzed using SPSS version 27, including a normality test, a homogeneity test, and a paired t-test. The research results showed significant improvement in dribbling speed after implementing training variations. The pre-test mean was 16.1610 seconds with a standard deviation of 1.18755, while the post-test mean was 14.9480 seconds with a standard deviation of 0.80772. The hypothesis test showed a significance value of 0.001 (< 0.05), indicating a significant difference between pre-test and post-test results. Dribbling training variations proved effective in improving futsal players’ ball dribbling speed. The training program can be used as an alternative method for coaches to enhance players’ technical skills systematically and continuously for optimal results.